The Effect Of Corporate Governance, Capital Intensity, And CSR On Financial Performance In The F&B Sector Listed On IDX 2021-2024 - Rafa Kamal Paresta; Sartika Wulandari (Golden Ratio of Auditing Research, 2026)
Financial performance describes how well the business can use its resources to profit. This quantitative research aims to ascertain elements that can affect financial performance, such as financial and non-financial ratios. Corporate governance, capital intensity, and corporate social responsibility are some indicators. For 2021-2024, IDX-listed firms operating in the food and beverage subsector comprised the population. The population consisted of 132 food and beverage sub-sector companies. A purposive sample strategy was used in this investigation. The research includes 24 different businesses. Data analysis uses EViews12 with a panel regression model. The study results show that corporate governance variables have a significant effect on ROA, capital intensity has no effect on ROA, and corporate social responsibility (CSR) has a negative and significant effect on ROA.